CIRRHOSIS OF LIVER: CASE STUDY - Mrs.C.JEGATHA (International Journal of Pharma and Bio Sciences, 2016)
Cirrhosis is a potentially life-threatening condition that occurs when scarring damages the liver. Cirrhosis harms the structure of the liver and blocks the flow of blood. The loss of normal liver tissue slows the processing of nutrients, hormones, drugs, and toxins by the liver. Also, the production of proteins and other substances made by the liver is suppressed. People with cirrhosis often have few symptoms at first. The person may experience fatigue, weakness, and exhaustion. Loss of appetite is usual, often with nausea and weight loss. As liver function declines, water may accumulate in the legs and the abdomen. Cirrhosis greatly increases the risk for liver cancer.Gastrointestinal (GI) bleeding can occur from abnormal blood clotting, which can be result of a combination of complications associated with cirrhosis.In severe cases, the disease causes encephalopathy (damage to the brain), with mental symptoms that range from confusion to coma and death.Hepatorenal syndrome occurs if the kidneys drastically reduce their own blood flow in response to the altered blood flow in the liver. It is a life-threatening complication of latestage liver disease that occurs in patients with ascites. Symptoms include dark colour urine and a reduction in volume, yellowish skin, abdominal swelling, mental changes (delirium, confusion), jerking or coarse muscle movement, nausea, and vomiting.Nearly all patients with cirrhosis are insulin resistant. Insulin resistance is a primary feature in type 2 diabetes and occurs when the body is unable to use insulin.About 30% of patients with chronic liver disease develop osteoporosis (loss of bone density), which is twice the usual incidence.